Table of Contents (Law, State and Telecommunications Review, 2020)
Dear Reader, We are pleased to present the second issue of the twelfth volume of the Law, State and Telecommunications Review (LSTR). In this special issue, the journal publishes a number of original articles on topics relevant to ICT and telecommunications in Latin America from a myriad of interdisciplinary perspectives. Several of the selected papers were presented at the XIII Communication Policy Research Conference Latin America (CPR Latam) held in the city of Cordoba, Argentina, July 1-2, 2019. We are delighted to include articles on the legal challenges presented by new digital business models, the legal nature of national data protection authorities, research platforms and the right to be forgotten, the responsiveness approach in European and Brazilian data protection regimes, data protection in the Paraguayan social security system, the regulation of subscription-based video streaming platforms, cyber security and personal data protection in the financial system, inequality in the dissemination and use of the internet in Brazil, and investments in telecommunication networks in the digital environment. In future issues, we will continue to publish articles on all relevant areas of ICT and telecommunications. We hope you will enjoy reading this issue, and we look forward to a thirteenth volume to be released on May 2021. Sincerely, Prof. Hernan Galperin Prof. Marcio Iorio Aranha Editors, The Law, State and Telecommunications Review